Information and measurement system for analyzing images of fundus tissue using computer-integrated technologies - Povstianoi, Oleksandr; Vynokurova, Olena; Denysiuk, Viktor; Lapchenko, Yurii; Hrudetskij, Roman (Ternopil-Opole, 2025)
The paper presents the results of research and development of a modern information and measurement system (IMS) designed for automated analysis of fundus images for the purpose of diagnosing and monitoring ophthalmic pathologies. The proposed system combines methods of digital medical image processing, artificial intelligence and computer vision, which allows ensuring high accuracy and objectivity of the diagnostic process. Particular attention is paid to the use of deep learning algorithms for the segmentation of anatomical structures of the retina and analysis of fluorescent images. A comprehensive method of photodynamic diagnostics and therapy has been developed, which is implemented based on a modified slit lamp with a laser illuminator. Effective methods of image registration and processing have been proposed, in particular their synchronization and spectral analysis, which allows for quantitative assessment of the state of tissues. The results of the study can be used in ophthalmological practice to increase the accuracy of early detection of pathologies, as well as in telemedicine and personalized medicine systems.
Information and measurement system for analyzing images of fundus tissue using computer-integrated technologies
The paper presents the results of research and development of a modern information and measurement system (IMS) designed for automated analysis of fundus images for the purpose of diagnosing and monitoring ophthalmic pathologies. The proposed system combines methods of digital medical image processing, artificial intelligence and computer vision, which allows ensuring high accuracy and objectivity of the diagnostic process. Particular attention is paid to the use of deep learning algorithms for the segmentation of anatomical structures of the retina and analysis of fluorescent images. A comprehensive method of photodynamic diagnostics and therapy has been developed, which is implemented based on a modified slit lamp with a laser illuminator. Effective methods of image registration and processing have been proposed, in particular their synchronization and spectral analysis, which allows for quantitative assessment of the state of tissues. The results of the study can be used in ophthalmological practice to increase the accuracy of early detection of pathologies, as well as in telemedicine and personalized medicine systems.
Keywords: Information and measurement system; ophthalmology; fundus imaging; deep learning; fluorescence diagnostics; photodynamic therapy; automated diagnostics 1